PENERAPAN TOKKATSU PADA TEMA 4 HIDUP BERSIH DAN SEHAT (STUDI NARATIVE INQUIRI PADA PEMBELAJARAN IPA KELAS 2 SEKOLAH DASAR DI MASA PANDEMI COVID-19) - Esih Yunengsih, - (2021)
In the current pandemic conditions, of course, personal hygiene and health and the surrounding environment are very important, therefore researchers here try to implement special activities or Tokkatsu in carrying out clean and healthy living during the covid-19 pandemic for children, to help achieve learning Theme 4 Clean and Healthy Living in Elementary School Science learning, as it is, goes hand in hand with conditions where everyone, especially students, must get used to living their daily lives while still implementing health protocols in accordance with government regulations. By prioritizing special activities that focus on clean and healthy living in the student environment, it will become a small-scale practice which they will later apply in the community, of course, to protect their environment with small steps or activities they do. The researcher uses the Narrative Inquiry method in which the form of delivery is in the form of a narrative or story, so as to accommodate the reader so that it is easier to understand the research results. This study discusses in depth about how to live a clean and healthy life during the current Covid-19 Pandemic, special student activities that focus on the cleanliness of their environment and shape their attitude of responsibility towards the environment in which they are located. Keywords: Tokkatsu, science learning, covid-19 pandemic.